Sport, Lebensalter und Gesundheit. Soziologische, leistungsbiographische, anthropometrische und medizinische Untersuchungen an Kraft-, Ausdauer- und Nichtsportlern im Seniorenalter - Kenntner, GeorgBuhl, BarbaraMenzel, Harald (Karlsruher sportwissenschaftliche Beiträge, 2006)
Significant changes in average life expectancy make it necessary to focus this study on the development of the physical capacity of humans in the aging process.On the basis of 178 different tests, 241 male test persons will be examined, 74 of them strength athletes, 112 endurance athletes and 55 non-athletes. All of the athletes surveyed are still active and members of the relevant national sports associations. The test persons are divided into two age groups (31 to 49 and 50 to 73 years).The tests collect data from the fields of sociology, performance biography, anthropology, anamnesis, motor skills, cardiovascular and lung function parameters at rest and under stress as well as fat and protein metabolism.The results should show the extent to which strength or endurance training or athletic inactivity influences the body at different stages of seniors and that gerontological research must increasingly have its place in the field of sports science.